Safety and effectiveness of iron sucrose therapy in paediatric patients with iron deficiency anaemia: a single-institution retrospective study - Shasha Zhao; Jingying Cheng; Liqiang Zhang; Jiafeng Yao; Jin Jiang (BMC Pediatrics)
Abstract Background Iron deficiency anaemia (IDA) is the most prevalent nutritional deficiency among children globally. Intravenous (IV) iron serves as an alternative treatment for paediatric patients with poor response to oral iron therapy. However, data on the use of IV iron sucrose treatment in Chinese children remain limited. Methods This retrospective study evaluated 40 paediatric patients with IDA (≤ 18 years) treated with IV iron sucrose at Beijing Children’s Hospital (July 2022-December 2023). Demographic, clinical, and laboratory parameters were analysed before and after therapy. Results Among the paediatric patients, 22 were male, 18 were female, and 19 were adolescent children older than 12 years. The average haemoglobin concentration increased from 75.6 g/L to 124.9 g/L, and the haematological response rates at both 4 and 8 weeks post-IV treatment were 100% and 97.5%, respectively. The average MCV increased from 67.6 fL to 82.4 fL, and the mean MCH increased from 18.8 pg to 26.5 pg. The mean MCHC increased from 276.2 g/L to 315.3 g/L. The median ferritin level increased from a pre-IV median of 5 ng/ml to a post-IV median of 85.9 ng/ml. Similarly, the serum iron level increased from a pre-IV median of 2.3 µmol/L to a post-IV median of 14.5 µmol/L. The mean TSAT increased appropriately from 2.9% pre-IV to 22.4% post-IV. A total of 36/40 children had a ferritin value greater than 30 ng/ml post-IV. The incidence of adverse reactions was 2.5% (1/40). Conclusion IV iron sucrose is safe and effective for Chinese paediatric patients with IDA who are unresponsive to oral iron.